Comparison of Manual Mode With Automatic Gas Control Mode for Sevoflurane Consumption in Maquet Flow-I Anesthesia Machine - Muhammad Jamil, Salman Shahzad, Shahbaz Hussain, Hamza Ali Bukhari, Anwar Ul Huda, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Inhalational anesthetic agents used for general anesthesia can have adverse effects on operation theater staff and environment. The innovative automated gas controller reduces inhalational anesthesia agent consumption. Aim: To compare sevoflurane consumption in manual mode versus automatic gas control (AGCTM) mode on Maquet Flow-i anesthesia machine in adult laparoscopic surgeries. Methods: This study was a randomized control trail conducted at Department of anesthesia, Security Forces Hospital Riyadh, Saudi Arabia and Pakistan Kidney and Liver Institute and Research Center, Lahore, Pakistan from December 2019 till December 2020. Sixty patients were randomly divided into two Groups A (Automatic Gas Control, AGCTM) and Group B (Manual Mode). Sevoflurane consumption and sevoflurane consumption rate was calculated in both groups. Data was analyzed using SPSS V.20. Results: Two groups were comparable in term of age, gender, and comorbidities. The mean sevoflurane consumption rate in group A was 23.92+4.6 as compared to 40.23+4.4 in group B (P=0.001). Similarly sevoflurane consumption rate is also statistically significant. (0.28 + 0.04 ml/min vs 0.47 + 0.02 ml/min, p=0.001) Conclusion: Sevoflurane consumption and sevoflurane consumption rate is lower in AGCTM mode as compared to manual mode of Maquet Flow-I anesthesia machine. Keywords: Sevoflurane, Maquet Flow-i, Automatic Gas Controller (AGCTM), Laparoscopic Surgeries